Effectiveness of Acceptance and Commitment-Based Schema Therapy on Depression and Treatment Adherence in Women with Multiple Sclerosis: A Quasi-Experimental Study - Hadad Ranjbar, Somayeh; Zare, Fahimeh (Psychology of Woman Journal, 2025)
Objective: The aim of the present study was to examine the effectiveness of acceptance and commitment-based schema therapy on treatment adherence and depression in women with Multiple Sclerosis (M.S). Materials and Methods: This research was a quasi-experimental study using a pre-test–post-test control group design. The statistical population included all women aged 20 to 50 with Multiple Sclerosis who had referred to the MS Association of Rafsanjan in 2024. After obtaining ethical approval, 30 participants were randomly selected and assigned to experimental and control groups. The experimental group received an intervention consisting of eight 45-minute therapeutic sessions, whereas the control group received no intervention. The instruments used in the study included the Beck Depression Inventory-II (BDI-II) and the Treatment Commitment Questionnaire (TCQ). Findings: The results indicated that the interaction effect for the post-test scores of treatment adherence (Group * Treatment Adherence) was 337.137 with an estimated error of 0.001, suggesting a statistically significant difference in the post-test scores of the experimental group in the variable of treatment adherence among women with MS. Similarly, the F-statistic for the interaction effect on depression (Group * Depression) was 934.55 with an estimated error of 0.001, also indicating a statistically significant difference in the post-test scores of the experimental group in the variable of depression among women with MS. Conclusion: The findings of the present study demonstrated that acceptance and commitment-based schema therapy is effective in improving treatment adherence and reducing depression in women with Multiple Sclerosis. Therefore, the use of this approach is recommended to enhance treatment commitment and alleviate depression in this population.